1985
DOI: 10.1002/stem.5530030605
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine growth factors for human tumor clonogenic cells

Abstract: A human epithelial-derived cell line, SW-13, releases a soluble substance that functions as an autocrine growth factor. SW-13 cells, derived from a human adenocarcinoma of the adrenal cortex, form a few small colonies when suspended in soft agar at low densities. The number of colonies increased significantly when either viable SW-13 cells or serum-free medium conditioned by SW-13 cells (CM) was added to agar underlayers. CM increased colony formation in a dose-dependent fashion. Clonal growth at low cell dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

1987
1987
1992
1992

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
5
1
Order By: Relevance
“…Previous studies from several laboratories (Halper and Moses, 1983;Hamburger and White, 1985) have demonstrated that SW-13 adrenal carcinoma cells produce factors that enhance clonal growth of this cell line in soft agar. We now provide evidence that much of the autocrine activity present in cell lysates is due to production of a mitogen indistinguishable from bFGF as judged by several criteria.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies from several laboratories (Halper and Moses, 1983;Hamburger and White, 1985) have demonstrated that SW-13 adrenal carcinoma cells produce factors that enhance clonal growth of this cell line in soft agar. We now provide evidence that much of the autocrine activity present in cell lysates is due to production of a mitogen indistinguishable from bFGF as judged by several criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Protein concentration was determined as described by Bradford ( 1976). ated as described by Hamburger and White (1985). Onemilliliter base layers of 0.5% agar (Difco, Detroit, MI) containing enriched McCoy's 5A medium were prepared in sterile plastic 35-mm Petri dishes.…”
Section: Purijkation Of Cell Extractsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their greater sensitivity could result from increased numbers of cell surface receptors and/or amplification of any of the various signal transduction path ways. In this sense, the acquisition of en hanced growth factor sensitivity would cor respond to a first step in the direction of an autocrine mechanism of growth control [4,5,18,19]. The transformed cells display their greatest sensitivity at low serum con centrations.…”
Section: Discussionmentioning
confidence: 99%